Vibration Control of Vehicle Seat Integrating with Chassis Suspension and Driver Body Model. Issue 1 (January 2013) - Du, Haiping; Li, Weihua; Zhang, Nong
Vehicle seat suspension is one of very important components to provide ride comfort, in particular, commercial vehicles, to reduce driver fatigue due to long hours driving. This paper presents a study on active control of seat suspension to reduce vertical vibration transmitted from uneven road profile to driver body. The control problem will be firstly studied by proposing an integrated seat suspension model which includes vehicle chassis suspension, seat suspension, and driver body model. This is a new concept in the field of study because most of the current active and semi-active seat suspension studies only consider seat suspension or seat suspension with human body model, and road disturbance is generally assumed to be applied to the cabin floor directly. Controller design based an integrated model will enable the seat suspension to perform in a scenario where vibration caused by road disturbance is transmitted from wheel to seat frame and ride comfort performance is evaluated in terms of human body instead of seat frame acceleration. A static output feedback controller is then designed for the seat suspension with using measurement available signals. Driver mass variation and actuator saturation are also considered in the controller design process. The conditions for designing such a controller are derived in terms of linear matrix inequalities (LMIs). Finally, numerical simulations are used to validate the effectiveness of the proposed control strategy. It is shown from the driver body acceleration responses under both bump and random road disturbances that the newly designed seat suspension can improve vehicle ride comfort regardless of driver body mass variation.